Research of Fault Diagnosis Method of Multi Low Speed High-loaded Bearings Installed on Same Axis - Han Jiahua; Yan Wen; Cao Jinhua (Jixie chuandong)
The multi low speed,high-loaded bearing installed on same axis,different locations of the bearing fault pulse will appear aliasing coupling phenomenon,resulting in fault signal identification difficult. In this regard,based on the characteristic of corner-domain and full vector empirical mode decomposition to identify and diagnose the vibration source of the low speed,high-loaded bearing fault signal is proposed. Firstly,the spline interpolation algorithm is used to transform the acquired time domain nonstationary signal into the angular pseudo-stationary signal to realize the angular area resampling,extract the contact angle of rotation of bearing,and the vibration source recognition is completed. Then,the signal is decomposed and reconstructed by EMD,the dual-channel full-spectrum technique is used to fuse the homologous information. Finally,the fault is identified by after chamfering domain analysis of the reconstructed signal,extract the characteristic parameters of contact times of per circle to complete the signal fault type diagnosis. The experimental results show that the fault diagnosis method based on characteristic of corner-domain and full vector EMD can satisfy the requirement of low speed,high-loaded fault signal diagnosis to a certain extent,and it has certain practicability.